Exosomes: Emerging Cell-Free Based Therapeutics in Dermatologic Diseases - Shi, Hui; Wang, Min; Sun, Yaoxiang; Yang, Dakai; Xu, Wenrong; Qian, Hui (Frontiers in Cell and Developmental Biology, 2021)
Exosomes are lipid bilayer vesicles released by multiple cell types. These bioactive vesicles are gradually becoming a leading star in cell-cell communication involving in various physiological and pathological process. Herein, we put the focus on the roles of exosomes under dermatologic conditions. Skin is the first line of our body defense system, of which the damage will bring significant discomfort to patients in appearance, functionality and even psychology. Exosomes from various origin take part in almost every link from cutaneous development to disorders. In this review, we will summarize the cutting-edge studies regarding exosome biology and their relationship with common dermatologic diseases including burn injury, aging, scars, diabetic wound, cutaneous tumors and the various molecular mechanisms are concretely elaborated. Furthermore, given the advantages of favorable biocompatibility and transporting capacity, the bioengineering modification of exosomes is also involved. However, as a new burgeoning field of medical science, there are still many unanswered questions about future exosome application. Rational understanding of the exosome biological properties and potential functions will provide new insight in the diagnostic markers and treatment of dermatologic diseases.